2013
DOI: 10.2169/internalmedicine.52.0278
|View full text |Cite
|
Sign up to set email alerts
|

Liver Dysfunction and Thrombocytopenia Diagnosed as Intravascular Large B-cell Lymphoma Using a Timely and Accurate Transjugular Liver Biopsy

Abstract: A 72-year-old man suffered from paraparesis with a sensory impairment and bladder and rectal disturbances. Magnetic resonance imaging T2-weighted images depicted a high-intensity lesion in the spinal cord that was consistent with myelitis. A blood examination revealed severe thrombocytopenia and liver dysfunction. No malignant cells were detected by peripheral smears or bone marrow biopsy. Systemic computed tomography detected hepatosplenomegaly and ascites but no lymphadenopathies. Transjugular liver biopsy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…The patient was successfully treated with chemotherapy following the histological diagnosis of hepatic IVL (13). However, due to the difficulty in confirming the suspicion of liver invasion using imaging studies and biopsy methods, to date the number of cases involving the liver diagnosed in the antemortem period is lower than that observed in the postmortem period (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) (Table). Our literature review of hepatic IVL cases diagnosed using imaging studies of the liver revealed that six of 10 cases were diagnosed at autopsy, and no specific findings were observed in the conventional CT studies (Table).…”
Section: Discussionmentioning
confidence: 99%
“…The patient was successfully treated with chemotherapy following the histological diagnosis of hepatic IVL (13). However, due to the difficulty in confirming the suspicion of liver invasion using imaging studies and biopsy methods, to date the number of cases involving the liver diagnosed in the antemortem period is lower than that observed in the postmortem period (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) (Table). Our literature review of hepatic IVL cases diagnosed using imaging studies of the liver revealed that six of 10 cases were diagnosed at autopsy, and no specific findings were observed in the conventional CT studies (Table).…”
Section: Discussionmentioning
confidence: 99%
“…[5] Lymphoma cells were positive for anti-CD20 antibody, but negative for CD3 and CD5 (Figs. 1C and D).…”
Section: Case Reportmentioning
confidence: 99%
“…3,6 Although, fever may be a presenting symptom, the clinical symptoms largely reflect the ischemic sequelae of intravascular occlusion associated with the proliferating intravascular tumor cells. [8][9][10][11][12][13][14][15][16][17][18] When patients present with disease confined exclusively to the skin (ie, the so-called cutaneous variant), they carry a much better prognosis than do those who present with skin disease in the setting of multiorgan involvement. Lymph node (LN) disease is seen in only 11% of cases.…”
Section: Introductionmentioning
confidence: 99%